Corais e comunidades recifais e sua relação com a sedimentação no Banco dos Abrolhos, Brasil - Ramos, Bárbara Segal (2003)
The effects of terrigenous sediments upon coral reefs are major concern all over the world. The aim of this study is to evaluate coral communities at different sediment settings at the Abrolhos Bank. Most reefs closer to shore presented higher sediment deposition rates than reefs farther from mainland. Deposition rates were, in most cases, higher at winter-spring and, usually, associated with the frequency of NE-E or S winds with speeds higher than 15 knots. This and the absence of differences in radioisotope composition of sediments in different seasons suggest an important influence of resuspention on the sedimentation regime. Coral communities showed no direct relation with sediment deposition. However, in most cases, reefs with high Palythoa caribaeorum cover also presented high sediment deposition rates. There was an inverse relation between P. caribaeorum abundance and coral cover. Nevertheless, reefs with different communities and sediment deposition rates presented high coral recruitment, and similar radioisotope assimilation by the coral Mussismilia braziliensis. Recruitment of hydrocorals presented a positive correlation with adult hydrocoral abundance, while scleractinian corais recruitment did not present the same pattern. Factors related to sedimentation, such as P. caribaeorum abundance or light, may be indirectly influencing the structure of coral communities. The occurence of different communities in apparently similar situations suggests these communities may respond to complex interactions of biotic and abiotic features, including the occurrence of stochastic events.